Implementasi Pelayanan Berbasis Elektronik di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu di Kota Batam - Agustina Sombo; Timbul Dompak (Komunitas Dosen Indonesia, 2023)
PTSP (One Stop Integrated Service) is an online licensing management system that makes use of a website-based application designed to deliver administrative public service online. The goal of this research is to examine the adoption of e-services and integrated one-stop services in investment offices. The methods employed are qualitative research approaches such as interviews, documentation, and observational data collecting. The results revealed that the deployment of e-services to improve public services in Batam City DPMPTSP was extremely good. High system security by using firewalls, passwords, and email verification. Development of Digital Ecosystem through OSS or Easy PTSP Online system that can enrich user experience and support the growth of digital economy in Batam City. DPMPTSP Batam City ideally provides quality services. Efficiency on the input side of the ease of accessing the PTSP website is clear and easy to find by license applicants. At PTSP Batam City, the licensing process through the online PTSP Easy System is now fast, cheap, simple, clear, guaranteed, and at an affordable price. Increased Competitiveness of Batam City through Online Single Submission (OSS) digital system. With OSS, businesses can avoid and reduce duplication of licensing processes. Data security Online licensing and non-licensing services also guarantee not to share the applicant's personal information with other parties or sites that are not related to the service.